Prevalence of Candida spp. among healthy denture and nondenture wearers with respect to hygiene and age - Bharathi Prakash; Malathi Shekar; Biswajit Maiti; Indrani Karunasagar; Sreeshma Padiyath (Wolters Kluwer Medknow Publications, 2015)
Dentures are inert and nonshading surfaces and therefore get easily colonized by Candida species. Subsequent biofilm produced by them lead to denture stomatitis and candidiasis. This study was aimed to understand the prevalence of Candida species among healthy denture and nondenture wearers with respect to their age and hygiene status. Swabs were collected from 50 complete dentures and 50 non-denture wearers and processed on Sabouraud's dextrose agar. Identification of Candida species was done by staining and a battery of biochemical tests. Data obtained was correlated with age & oral hygiene and statistical analysis was performed. Candida was isolated from both denture and nondenture wearers. Prevalence of different Candida species was significantly higher in denture wearers and found predominated by C. albicans, C. tropicalis, C. dubliensis and C. glabrata. Among nondenture wearers, C. albicans and C. tropicalis were isolated. Prevalence of Candida increased with increasing age among denture wearers. Men presented declining denture hygiene compared to women with increasing age. In comparison to nondenture wearers, multispecies of Candida colonized the dentures thus presenting higher risk of candidiasis especially with increasing age.